Seasonal Baltic Sea level change from altimetry data - Pajak, Katarzyna (International Conference “Environmental Engineering”, 2017)
Regional sea level changes occur at different time scales. Global warming of the oceans, glacial and polar ice melting and meteorological or hydrological factors are major contributors to long-term sea level rise. In the recent years, a lot of attention has been paid to research concerning sea level change and seasonal fluctuations. The main objective of this paper was to determine the seasonal variability in the Baltic Sea level using satellite altimetry data for the period 1 January 2010 – 31 December 2014. The ANOVA analysis of variance was used in the re search in order to estimate seasonal fluctuations. This study focused on investigate the monthly and annual amplitude in sea level anomalies over a given time period. The results from research showed that the amplitudes of fluctuations are the highest in winter and the smallest in summer in three analyzed points of the Baltic Sea. The results can bring valuable information about ongoing aspects in sea level changes, as a way of tracking climate change.